Case Report: Long-Term Outcome Following Maximal Partial Resection in a Primary Pericardial Lymphangiohemangioma - Song, Long; Daniel Iroegbu, Chukwuemeka; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Cardiac tumors are significantly rare, with pericardial hemangiolymphangioma amongst the rarest cardiac tumor types, with very few reported cases in the literature. Clinically, lymphangiohemangiomas are generally deemed unresectable due to its proximity to the myocardium and the uncertainty of the outcomes following subtotal resection. Case report: Herein, we report a case of a 40-year-old man diagnosed with a pericardial mass, dull thoracodorsal pain, and over a 10-years history of palpitation. Notably, the pericardial mass in the present case was found extended within the myocardium. Thus, a maximal safe resection was deemed preferable to a total resection. The surgically resected specimen showed pathological characteristics of a lymphangiohemangioma. After surgical resection of the lymphangiohemangioma, the patient was free of any tumor-related symptoms. Also, there was no evident tumor progression after a 4-year postoperative follow-up. Conclusion: To the best of our knowledge, the present case study is the first in the literature to report on a long-term postoperative outcome following subtotal resection of a pericardial lymphangiohemangioma.